1985
DOI: 10.1071/ea9850117
|View full text |Cite
|
Sign up to set email alerts
|

The capeweed content of pastures in south-west Western Australia

Abstract: The capeweed (Arctotheca calendula) content of pastures in the agricultural areas of Western Australia was estimated from coloured aerial photographs taken during flowering. Linear regressions were obtained between a visual score for capeweed content based on colour and the actual capeweed content of calibration sites. Surveys in 1972, 1973 and 1975 showed that 1973 was a year of high capeweed content in all areas compared with 1972 and 1975. The content was higher in lower-rainfall wheatbelt areas, where it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…The potential of remote sensing to identify and monitor weed infestations has been studied using aerial photography (Arnold et al, 1985;Everitt et al, 1996), multispectral imagery, such as Landsat Thematic Mapper (Dewey et al, 1991;Gardiner et al, 1998;Taylor, 1990) and multispectral digital video systems (Lamb et al, 1999;Lass and Callihan, 1997;Richardson et al, 1985) with mixed success (McGowen et al, 2001). In particular, Ullah et al (1989) and Frazier (1998) showed that high-spatial-resolution multispectral data could be utilized to produce accurate maps of blackberry distribution.…”
Section: Previous Remote Sensing and Spectral Implicationsmentioning
confidence: 98%
“…The potential of remote sensing to identify and monitor weed infestations has been studied using aerial photography (Arnold et al, 1985;Everitt et al, 1996), multispectral imagery, such as Landsat Thematic Mapper (Dewey et al, 1991;Gardiner et al, 1998;Taylor, 1990) and multispectral digital video systems (Lamb et al, 1999;Lass and Callihan, 1997;Richardson et al, 1985) with mixed success (McGowen et al, 2001). In particular, Ullah et al (1989) and Frazier (1998) showed that high-spatial-resolution multispectral data could be utilized to produce accurate maps of blackberry distribution.…”
Section: Previous Remote Sensing and Spectral Implicationsmentioning
confidence: 98%
“…The botanical composition of annual pastures varies markedly from year to year depending on rotation, cultivation, management, environmental conditions at seed set and the timing of the break of season (Arnold et al ., 1985; Arnold and Anderson, 1987; Bolger et al ., 1995; Thomson et al ., 1998). The Mediterranean‐type climate of south‐western Australia is characterized by hot dry summers and cool wet winters (Turner, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Harris and Haney 1973), and later extended to detect weeds in crops and pastures (Barrett and Leggett 1979;Arnold et al 1985). However, limitations of aerial photography for crop monitoring include the absence of a quantitative data acquisition capability, the high cost and limited availability of colour infrared film and processing, and the requirement for manual scanning or digitising for incorporation into a Geographic Information Systems (GIS) package.…”
Section: Airborne Multispectral Imaging Systemsmentioning
confidence: 98%